The Oldest Zero and Decimal Numeral System in the World: Vietnam, Cambodia or Indonesia? - Mohd. Zain, Shaharir bin (Indonesian Journal of Mathematics and Natural Sciences, 2025)
Aczel (2013a,b) and ealier Ifrah (1998) claimed that the oldest zero in the world is from the Old Khmer-Cambodia and Campa-Vietnam respectively even though Diller (1995) and more detail, Shaharir (2001) have shown that Zero from Sriwijaya Kingdom in Sumatra, Indonesia, is as at least as old as the Old-Khmer Zero. Then Shaharir and Zahrin (2019)  provide strong arguments  that the Sriwijaya Zero is the oldest and simultaneously give reasons behind the error made by Aczel and Ifrah. However, inspired by verbal comments of our readers we have reexamined our paper and indeed found some weaknesses in our arguments. This paper explains those short comings and make a thorough and rigourous amendments and improvements. We now believe even stronger that the oldest decimal numeral system containing zero in the world is from Sumatera, Indonesia, which was invented in the 7th Century AD.